Assignment Procedure Biases in Randomised Policy Experiments1. (5th July 2016) - Aldashev, Gani; Kirchsteiger, Georg; Sebald, Alexander
Abstract : Randomised controlled trials (RCT) have gained ground as the dominant tool for studying policy interventions in many fields of applied economics. We analyse theoretically encouragement and resentful demoralisation in RCTs and show that these might be rooted in the same behavioural trait – people's propensity to act reciprocally. When people are motivated by reciprocity, the choice of assignment procedure influences the RCTs' findings. We show that even credible and explicit randomisation procedures do not guarantee an unbiased prediction of the impact of policy interventions; however, they minimise any bias relative to other less transparent assignment procedures.